2015
DOI: 10.1515/hukin-2015-0124
|View full text |Cite
|
Sign up to set email alerts
|

Positional Role Differences in the Aerobic and Anaerobic Power of Elite Basketball Players

Abstract: The aim of the present study was to compare the aerobic and anaerobic power and capacity of elite male basketball players who played multiple positions. Fifty-five healthy players were divided into the following three different subsamples according to their positional role: guards (n = 22), forwards (n = 19) and centers (n = 14). The following three tests were applied to estimate their aerobic and anaerobic power and capacities: the countermovement jump (CMJ), a multistage shuttle run test and the Running-base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
42
0
8

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(53 citation statements)
references
References 27 publications
3
42
0
8
Order By: Relevance
“…Basketball team playing positions are in general classified into three playing specific positions: guards, forwards and centers (Ben Abdelkrim, Chaouachi, Chamari, Chtara, & Castagna, 2010). Prior research has reported differences between positional roles in aerobic and anaerobic power (Pojskić, Šeparović, Užičanin, Muratović, & Mačković, 2015), maximal aerobic power (Cormery, Marcil, & Bouvard, 2008;Ostojic, Mazic, & Dikic, 2006;Sallet, Perrier, Ferret, Vitelli, & Baverel, 2005), speed (Smith & Thomas, 1991), height (Ackland, Schreiner, & Kerr, 1997;Bale, 1991;Ostojic, et al, 2006;Sallet, et al, 2005), body mass (Latin, et al, 2009;Ostojic, et al, 2006;Sallet, et al, 2005) and body fat (Latin, Berg, & Baechle, 2009;Ostojic, et al, 2006;Sallet, et al, 2005) in men's senior basketball. However, positions should attend to the specific role within the competition: point guard (PG), shooting guard (SG), small forward (SF), power forward (PF) and center (C) .…”
Section: Introductionmentioning
confidence: 99%
“…Basketball team playing positions are in general classified into three playing specific positions: guards, forwards and centers (Ben Abdelkrim, Chaouachi, Chamari, Chtara, & Castagna, 2010). Prior research has reported differences between positional roles in aerobic and anaerobic power (Pojskić, Šeparović, Užičanin, Muratović, & Mačković, 2015), maximal aerobic power (Cormery, Marcil, & Bouvard, 2008;Ostojic, Mazic, & Dikic, 2006;Sallet, Perrier, Ferret, Vitelli, & Baverel, 2005), speed (Smith & Thomas, 1991), height (Ackland, Schreiner, & Kerr, 1997;Bale, 1991;Ostojic, et al, 2006;Sallet, et al, 2005), body mass (Latin, et al, 2009;Ostojic, et al, 2006;Sallet, et al, 2005) and body fat (Latin, Berg, & Baechle, 2009;Ostojic, et al, 2006;Sallet, et al, 2005) in men's senior basketball. However, positions should attend to the specific role within the competition: point guard (PG), shooting guard (SG), small forward (SF), power forward (PF) and center (C) .…”
Section: Introductionmentioning
confidence: 99%
“…It is reasonable to expect that positional specifics in physical attributes and playing duties will be reflected in position-specific differences in jumping performance. Pojskic et al reported CMJ of 40.40±5.04, 37.62±6.80, and 36.04±3.80 cm for Guards, Forwards and Centres, respectively, with significant ANOVA differences between Centres and the other two positions [ 20 ]. Similarly, Ben Abdelkrim et al found the lowest CMJ for players involved in frontcourt duties (41.6±4.2 and 40.9±3.7 cm for Centres and Power Forwards) in comparison to backcourt players (50.2±5.9, 48.4±5.1, 52.5±5.0 for Point guards, Shooting guards and Small forwards, respectively) [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Aggressive, quick, active, and explosive characteristics of basketball [1] should be surely supported by good physical abilities. One of that is aerobic endurance.…”
Section: Introductionmentioning
confidence: 99%